Meta-Analysis: The Impact of Problem-Based Learning (PBL) Models on Students' Critical Thinking Skills - Hafizah, May; Solin, Sogya; Purba, Cindy Theresia; Sihotang, Melda Maranata; Rahmad, Riki; Wirda, Mona Adria (Journal of Digital Learning and Education, 2024)
Critical thinking is an essential skill in the modern information era, enabling individuals to analyze complex information, evaluate arguments, and make informed decisions. In educational contexts, particularly in geography, fostering critical thinking equips students to address real-world environmental and social challenges. Problem-Based Learning (PBL) has emerged as a transformative teaching approach to develop these cognitive abilities through active, problem-centered learning. This meta-analysis aimed to evaluate the effectiveness of PBL in enhancing students' critical thinking across various educational levels. Using OpenMEE software and a continuous random-effects model, the study synthesized findings from 20 peer-reviewed studies published between 2020 and 2024. Statistical analyses focused on the standardized mean difference (SMD) as the primary metric to measure effect sizes. The results demonstrated that PBL significantly enhances critical thinking skills, with an overall SMD of 1.254 (95% CI: 0.875 to 1.633, p < 0.001). However, notable heterogeneity was observed, attributed to variations in educational levels, implementation fidelity, and study contexts. Subgroup analyses revealed that junior high school students experienced the greatest improvement, followed by university, senior high school, and elementary school students. These findings affirm PBL’s potential as an effective pedagogical strategy for fostering critical thinking. The study highlights the need for tailored PBL implementations and further research into its long-term effects and applicability across diverse educational contexts. The results provide robust evidence supporting PBL as a vital tool in modern education.